An Environment‐friendly Synthesis of 2, 3‐Disubstituted‐2‐iminothiazoline‐4‐ones. (11th May 2015) - Meng, Ge; Zheng, Meilin; Dong, Mengshu; Wang, Mei; Zheng, Aqun; Guo, Zengjun
Abstract : A series of 2, 3‐substituted‐2‐iminothiazoline‐4‐ones derivatives have been synthesized via an improved method including an auto‐catalyzed reaction. This method avoided using any extra catalyst except for the reaction material. This method has been successful in both the aromatic substituted 2‐iminothiazolines and the alkyl substituted 2‐iminothiazolines. The special product with a hydroxyl group on the 2‐iminogroup of 1, 3‐thiazoline‐4‐ones has also been obtained unexpectedly. The possible mechanism has been proposed for the special process ofdealkylation andhydroxylation . This method offered a special way to afford the 2‐hydroxyimino‐substituted thiazoline‐4‐one derivatives in an efficient and eco‐friendly way. The mechanism of the transformation under acid condition has also been proposed. Abstract :